PENGEMBANGAN BAHAN AJAR IPA TERPADU TEMA "MUSIM PADA BUDAYA LOMBOK" DENGAN METODE 4STMD - Pebriyanti, Dwi (2017)
Teaching materials is a component in teaching learning that will determine the success of learning. The aim of science learning is to make students understand the environment and its culture from science perspectives. Therefore, teaching materials that lift lokal content is needed. So, students can understand their culture and environment surroundings of the science perspective. This research is research and development (RdanD) which aimed to produce science teaching material and to examinethe characteristics of its development, comprehension, feasibility and its influence to change student understanding. Science teaching materials which developed in this study themed 'Season on Lombok Culture'. The main matter is system of calculation of seasons (mangse) done by Lombok people, nyale dan bau nyale tradition, and influence of season on ecosystem in Lombok. This science teaching materials 'Season on Lombok Culture' were developed by 4STMD (Four Steps Teaching Material) method, which was composed of 4 stages of selection, structuring, characterization and didactic reduction. At each stage of development carried out quality control with the reviu of the expert.This teaching materials tried out toward 136 junior high school students in Lombok and the result shows that 91% of the material in this teaching material is easy according to the students, while based on the writing basic idetest, we know that 98% of material is easy criteria and the remaining 2% is medium. Besides that, the feasibility test conducted by 7 science teachers in Lombok shows that this teaching material meets the eligible criteria of the content, language, presentation and design aspects with an average percentage of 82.2%. Implementation of this science teaching materials conducted by 46 junior high school students in Lombok indicates that this teaching material can improve students understanding on all subjects with an average N-gain <g ̅> 0.4 which means its influence on improving students' understanding is medium. ----------- Bahan ajar merupakan salah satu komponen dalam pembelajaran yang sangat menentukan keberhasilan suatu pembelajaran. Pembelajaran IPA bertujuan agar siswa memahami lingkungan dan budayanya dari perspektif IPA. Bahan ajar IPA yang mengangkat konten lokal sangat dibutuhkan agar siswa dapat memahami budaya dan alam sekitarnya dari perspektif IPA. Penelitian ini adalah penelitian Research and Development yang bertujuan untuk menghasilkan sebuah bahan ajar dan mengkaji karakteristik pengembanganya, keterpahamannya, kelayakannya dan pengaruhnya terhadap perubahan pemahaman siswa. Bahan Ajar IPA terpadu yang dikembangkan pada penelitian ini bertema'Musim pada Budaya Lombok'. Materi utamanya adalah sistem perhitungan musim (mangse) yang dilakukan masyarakat Lombok, nyale dan tradisi bau nyale dan pengaruh musim terhadap ekosistem di Lombok. Bahan ajar IPA terpadu 'Musim pada Budaya Lombok' ini dikembangkan dengan metode 4STMD (Four Steps Teaching Material Development), yang terdiri dari 4 tahap, yaitu seleksi, strukturisasi, karakterisasi dan reduksi didaktik. Pada setiap tahap pengembangan dilakukan kontrol kualitas dengan adanya review dari ahli. Bahan ajar "Musim pada Budaya Lombok" ini diuji keterpahamannya oleh 136 siswa SMP di Lombok dan hasilnya menunjukkan bahwa 91% materi pada bahan ajar ini mudah menurut siswa. Sedangkan berdasarkan tes penulisan ide pokok, 98% materi termasuk kriteria mudah dan sisanya 2% sedang. Uji kelayakan yang dilakukan oleh 7 orang guru IPA di Lombok menunjukkan bahwa bahan ajar ini memenuhi kriteria layak dari aspek isi, bahasa, penyajian, dan kegrafikan dengan presentase rata-rata 82,2%. Uji coba bahan ajar dilakukan oleh 46 siswa SMP di Lombok. Hasilnya menunjukkan bahwa bahan ajar ini dapat meningkatkan pemahaman konsep siswa pada semua pokok bahasan dengan N-gain rata-rata <g ̅> sebesar 0,4. Artinya, pengaruhnya terhadap peningkatan pemahaman konsep siswa tergolong sedang.